The Impact of Coronavirus to Terrorist Offenders in Indonesia: Assessments on psychological risk profiles before and during pandemic - Zora Arfina Sukabdi (Asosiasi Psikologi Forensik (Apsifor), 2022)
City lockdowns during the Coronavirus pandemic were seen by terrorism networks as authorities’ attempt to limit people’s access to places of worship and secularise people, as well as a sign of a forthcoming apocalypse. Several arrestments of terror actors in Indonesia during the pandemic raised the question of whether the physical restrictions ever reduced the criminogenic risks of terrorist network’s members. This study aims to investigate the impact of the Covid-19 pandemic on 18 terrorist profiles in Indonesia. The study assesses the psychological criminogenic risks of terrorist offenders in Indonesia before and during pandemic. Both quantitative and qualitative analysis was used to examine the risk assessment. The findings indicate no significant difference in the total scores of offenders’ risks before and during the pandemic. However, the qualitative risk profiles demonstrate the changes in offenders’ motivation, ideology, and capability.